Managing operations : your guide to getting it right (Profile Books, 2015)
The best operations management ensures that a business's infrastructure and processes balance efficiency with effectiveness, using the right resources to maximum effect. Using the series' trademark mix of checklists and thinker profiles, CMI experts guide the reader through the fundamentals of some key operational issues: quality control and management; change and project management; the supply chain and monitoring and control. Topics covered include: getting TQM to work, benchmarking, project risk assessment, outsourcing, inventory and purchasing, strategic risk management.